Linking Mercury Contamination to Transport Dynamics in an Indonesian River: A Data-Driven Engineering Framework for ASGM-Impacted Watersheds - Rindi Genesa Hatika; Indang Dewata; Ria Karno; Ika Daruwati; Fadhila Hidayah (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
While Artisanal and Small-Scale Gold Mining (ASGM) severely contaminates watersheds with mercury (Hg), existing studies primarily diagnose pollution levels without identifying the underlying transport mechanisms or actionable engineering solutions. Addressing this gap, this study analyzes Hg concentrations, identifies physical transport vectors, and proposes a data-driven mitigation framework for the Kuantan River, Indonesia. A targeted spatial sampling (n=10) was conducted during the dry season (June 2025), with water samples analyzed using Cold Vapour Atomic Absorption Spectrometry (CVAAS). Results revealed gross contamination, with 100% of samples exceeding the World Health Organization (WHO) limit of 0.001 mg/L (ranging from 0.0027 to 0.0081 mg/L). The Heavy Metal Toxicity Load (HMTL) indicated critical toxicological risks (3.94–11.81). Crucially, Principal Component Analysis (PCA) identified Total Dissolved Solids (TDS) as the dominant spatial transport vector, demonstrating that Hg is predominantly particulate-bound rather than dissolved. To mitigate this, a hierarchical engineering framework is proposed, featuring source control (mercury-capturing retorts), pathway interruption (sedimentation basins to trap TDS), and receptor protection (point-of-use filtration). Although limited by a small sample size, this study extends foundational environmental engineering knowledge by linking statistical transport diagnostics to structural interventions, offering a replicable policy and watershed management blueprint for ASGM-impacted regions globally.